“Come, Dark-eyed Sleep”: Michael Field and the Performance of the Lyric as a Radical Fantasy - Mayron Estefan Cantillo Lucuara (Revista Alicantina de Estudios Ingleses, 2021)
This article seeks to illustrate how the Michael Fields articulate their Sapphic poetry in Long Ago (1889) not only in keeping with their own Shakespearean aspirations and with Robert Browning’s hybrid formula of dramatic lyrics, but also in connection with Jonathan Culler’s theory of the lyric as a performative genre. Much recent scholarship has broken ground in the rediscovery and reappraisal of the Fields’ literary stature, yet the general critical approach has been divisive in addressing their poetry and their verse dramas separately. Some critics have taken heed of how their lyrics in general exhibit an intrinsic dramatic temper, yet no systematic inquiry has discussed how this lyrical dramaticity is manifest in any particular instance. Thus, this article singles out Long Ago’s second poem for its powerful performative energy, offering a close reading of each line, and demonstrating that it amounts to a hybrid dramatic lyric, as well as a tragic and transgressive performance in which a new Sappho takes centre stage as a Dionysian apologist of radical erotic fantasies.